Determination of Base and Non Base Sector of Livestock Commodity Development in Southeast Sulawesi Province, Indonesia - Sandiah, Natsir; Aku, Achmad Selamet; Sani, La Ode Arsad; Nafiu, La Ode; Munadi, La Ode Muh. (Technium Social Sciences Journal, 2021)
This research was conducted in Southeast Sulawesi Province, aiming to determine the basic and non-base sectors of livestock commodity development which can be used as livestock development areas. The data used are secondary data. Meanwhile, LQ analysis (location quotient) is a method used to determine the potential development and growth of livestock commodities in each district. The results showed that large livestock in the form of beef cattle were spread over 6 districts, dairy cows in 2 districts, buffalo in 5 districts, goat in 8 districts, pigs in 5 districts, and horses in 4 districts, each of which had LQ> 1. Meanwhile, small livestock in the form of native chickens are spread over 6 districts, 6 laying hens in 6 regencies, 6 regencies of broilers, 5 regencies of ducks and 7 regencies of manila ducks with LQ> 1